Albania : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the report on the observance of standards and codes on the financial action task force (FATF) recommendations for antimoney laundering and combating the financing of terrorism for Albania was prepared by a team of the International Monetary Fund using the assessment methodology adopted by the financial action task force. The assessment is based on the information available at the time of the mission and other verifiable information subsequently provided by the authorities. The detailed assessment report on which this document is based was adopted by the MONEYVAL plenary.